DNA synthesis in polyoma virus infection. III. Mechanism of inhibition of viral DNA replication by cycloheximide. - Yu, K (1975)
The formation of viral DNA was inhibited in polyoma virus-infected cells in which protein synthesis had been blocked by cycloheximide. The present studies show the following. (i) The pool of replicating viral DNA molecules was reduced in cycloheximide-treated cells by an amount consistent with inhibition of [3-H]thymidine incorporation into viral DNA, whereas the rate of turnover of the replicating population was not affected. (ii) The rate of conversion of replicating molecules into closed-circular DNA was not affected by cycloheximide. (iii) The rate of elongation of nascent viral DNA fragments into strands of unit genome length was unaffected by cycloheximide. It is concluded that viral DNA synthesis is inhibited in the absence of protein synthesis exclusively at the level of initiation of new rounds of genome replication. Replicating molecules already initiated at the time of addition of cycloheximide matured into progeny closed-circular DNA at a normal rate.